Indonesia’s Strategic Diplomacy and BRICS Membership: Opportunities and Risks in a Multipolar Global Order - Darwis, Danial; Setiawan, Aria Aditya (Global South Review, 2025)
This article analyses Indonesia’s strategic diplomatic manoeuvre in joining BRICS amidst the growing multipolarity of the global order. Using a qualitative case study approach, this paper integrates three key frameworks: Free and Active Foreign Policy, Hedging Strategy, and Multipolarity. The study draws on secondary data from government documents, academic journals, think-tank reports, and international media sources. The findings reveal that Indonesia’s accession to BRICS opens strategic opportunities in South–South economic cooperation, access to alternative development financing, and enhanced geopolitical influence. However, it also presents diplomatic risks such as potential Western pressure, internal dominance within BRICS by major powers, and reputational shifts that may affect ASEAN cohesion. The paper argues that Indonesia adopts a calculated hedging strategy that balances bilateral ties and multilateral engagement to maintain strategic autonomy. This study contributes to existing literature by offering an integrated analytical framework to understand Indonesia’s foreign policy adaptation, while also providing practical insight into the dynamics of middle power diplomacy in the Global South.